Hybridization of additive manufacturing processes to build ceramic/metal parts: Example of HTCC. Issue 3 (March 2021) - Raynaud, Jonathan; Pateloup, Vincent; Bernard, Mégane; Gourdonnaud, Delphine; Passerieux, Damien; Cros, Dominique; Madrangeas, Valérie; Michaud, Philippe; Chartier, Thierry
Abstract: Stereolithography is an additive manufacturing process, which makes it possible to fabricate useful complex 3D ceramic parts with a high dimensional resolution, a good surface roughness and properties close to those obtained by classical routes. Previous work concerning LTCC components, demonstrates that it is possible, by coupling the stereolithography with robocasting additive processes, to obtain multi-material components (e.g. ceramic / metal components). On the base of this previous work, the manufacturing of HTCC components using this innovative hybrid additive manufacturing process is described. Various complex and innovative geometries of HTCC alumina/tungsten components, in order to improve the characteristics of current circuits, are built and the mechanical and electrical properties characterized. Finally, hyper-frequency parameters of simulated HTCC complex micro strip resonators were compared to measured values on components manufactured by additive manufacturing.